Our experience of management of sub trochanteric fractures of femur by proximal femoral nail - Batra, Ashish Vinod; Singh, Harpreet; Challa, Supradeeptha; Rao, M .V. Ramanna (International Journal of Research in Medical Sciences, 2017)
Background: Sub trochanteric fractures of the femur remain some of the most challenging fractures. Most of the fractures result from trivial fall in the elderly; while in the younger age group, it's mainly due to road traffic accidents. Operative management is the preferred treatment. This study is intended to assess the outcome of the intramedullary fixation of sub trochanteric fractures with Proximal Femoral Nail (PFN). Methods: This study is a prospective, uncontrolled study of 40 cases of sub trochanteric fracture of femur admitted to a tertiary level hospital between August 2011 and November 2013; and treated with proximal femoral nails. Adults with recent sub trochanteric fracture of femur were included in this study; while patients less than eighteen years of age, pathologic fractures, periprosthetic fractures, and old neglected fractures were excluded from the study. Results: In our study of 40 cases, there were 28 male and 12 female patients with mean age of 51.43 years (range 22-87 years). Based on Seinsheimer’s classification, type IIIA fractures accounted for majority (32.5%) of the cases. majority of patients, i.e. 35% (n=14) showed union at 20 weeks after surgery. Cases were followed up and assessed according to the Harris hip scoring system (Modified).The outcome was good to excellent in 82.9% cases. Conclusions: From our study we conclude that PFN is a reliable minimally invasive implant for sub trochanteric fractures, with good to excellent functional outcome in the majority of cases.